Impact of perioperative blood transfusion on long-term survival in patients with different stages of perihilar cholangiocarcinoma treated with curative resection: A multicentre propensity score matching study - Liu, Zhi-Peng; Cheng, Zheng-Jun; Dai, Hai-Su; Zhong, Shi-Yun; Zhao, Dong-Chu; Gong, Yi; Zuo, Jing-Hua; Che, Xiao-Yu; Chen, Wei-Yue; Wang, Zi-Ran; Yu, Ting; Cheng, Jun-Jie; et al. (Frontiers in Oncology, 2022)
Background & Aim The association of perioperative blood transfusion(PBT) with long-term survival in perihilar cholangiocarcinoma(pCCA) patients after surgical resection with curative intent is controversial and may differ among different stages of the disease. This study aimed to investigate the impact of PBT on long-term survival of patients with different stages of pCCA. Methods Consecutive pCCA patients from three hospitals treated with curative resection from 2012 to 2019 were enrolled and divided into the PBT and non-PBT groups. Propensity score matching(PSM) was used to balance differences in baseline characteristics between the PBT and non-PBT groups. Kaplan–Meier curves and log-rank test were used to compare overall survival(OS) and recurrence-free survival(RFS) between patients with all tumor stages, early stage(8th AJCC stage I), and non-early stage(8th AJCC stage II-IV) pCCA in the PBT and non-PBT groups. Cox regression analysis was used to determine the impact of PBT on OS and RFS of these patients. Results 302 pCCA patients treated with curative resection were enrolled into this study. Before PSM, 68 patients(22 patients in the PBT group) were in the early stage and 234 patients(108 patients in the PBT group) were in the non-early stage. Patients with early stage pCCA in the PBT group had significantly lower OS and RFS rates than those in the non-PBT group. However, there were with no significant differences between the 2 groups with all tumor stages and non-early stage pCCA. After PSM, there were 18 matched pairs of patients with early stage and 72 matched pairs of patients with non-early stage. Similar results were obtained in the pre- and post-PSM cohorts: patients with early stage pCCA in the PBT group showed significantly lower OS and RFS rates than those in the non-PBT group, but there were no significant differences between the 2 groups for patients with all tumor stages and non-early stage pCCA. Cox regression analysis demonstrated that PBT was independently associated with worse OS and RFS for patients with early stage pCCA. Conclusions PBT had a negative impact on long-term survival in patients with early stage pCCA after curative resection, but not in patients with non-early stage pCCA.